An Investigation Into How Motivational Factors Differed Among Individuals Engaging in CrossFit Training. (September 2018) - Feito, Yuri; Brown, Chris; Box, Allyson; Heinrich, Katie M.; Petruzzello, Steven J.
With few adults completing recommended levels of aerobic and muscle-strengthening activities, it is important to examine the motives of those who do, as well as how those motives might differ by participation frequency. Considering the rapid growth of CrossFit Training (CFT), we examined CFT participation motives in individuals training at different frequencies. Adults ( N = 732) with >3 months of CFT experience completed an online version of the Exercise Motivations Inventory–2 (EMI-2). Significant correlations were seen between CFT frequency and all EMI-2 variables except for those related to health pressures, ill-health avoidance, and appearance. Kruskal–Wallis tests showed individuals training <3 days/week scored lowest on enjoyment, affiliation, and competition motives. Those training >5 days/week scored highest on challenge, social recognition, strength and endurance, and nimbleness motives, but lowest on weight management. Our results suggest that CFT participants who trained more frequently report motives that satisfied competence, autonomy, and relatedness needs.